Nanotheranostics: The Fabrication of Theranostics with Nanoparticles and their Application to Treat the Neurological Disorders - Singh, Astha; Patel, Aakriti; Chaudhary, Hema; Yadav, Kiran; Minocha, Neha (Recent Patents on Nanotechnology, 2025)
BackgroundTheranostics is a method that focuses on providing patient-centred care and is evolving as a targeted, safe, and effective pharmacotherapy. Nanotheranostics combines diagnosis and therapeutic modalities that bridge traditional treatment and personalised medicine. Theranostics provides novel ideas for nanotechnology. This review describes the current state of nanotechnology-based therapies used to treat neurological illnesses. Some patents on theranostics are also discussed in this review.ObjectiveThis study aims to provide a more comprehensive review of the diagnosis and therapeutic properties of nanotheranostics, the present state of nanotechnology-based treatment of neurological disorders, and the future potential of theranostics.MethodsThe phrase “theranostics” refers to a treatment strategy that integrates therapeutics and diagnostics to monitor treatment response and enhance drug efficacy and safety. Theranostics is a crucial component of personalised medicine and calls for significant advancements in predictive medicine. The term “theranostics” refers to a diagnosis that screens patients for potential adverse drug reactions and targets drug delivery depending on the test results. Theranostics treats neurological disorders (like brain tumours (glioma), Parkinson's disease, Alzheimer's disease, and neurovascular diseases). Many review articles on Google Scholar, PubMed, Google Patents, and Scopus were used to gather information for this review. Data acquired from many sources was compiled in this review to provide more information on theranostics.ResultsThe role of various nanocarrier systems as theranostic agents for neurological illnesses and the fabrication of nanomaterials for theranostics are discussed in this article after evaluating a substantial number of review articles.ConclusionThe distinctive intrinsic features of nanoparticles make them useful for functionalization and imaging. Theranostics in nuclear medicine include diagnostic imaging and therapy using the same molecule that is radiolabeled differently or the same medication at various doses. It is possible to determine if a patient will benefit from a given treatment by visualising potential targets. Targeted nuclear therapy has been shown to be beneficial in patients if chosen carefully and has a good safety profile.
Keywords: theranostics